Bacillus Calmette-Guerin, Mycobacterium bovis, as an immunomodulator in atopic diseases - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2006)
Based on the hygiene hypothesis association between atopy and bacillus Calmette-Guerin (BCG), purified protein derivative skin test reaction, mycobacterial disease, and environmental mycobacteria are summarized. The role of mycobacterial species in the activation of the innate immune response through Toll-like receptors is mentioned. The implications and perspectives of BCG as a potential therapeutic adjuvant in atopic disease are discussed.
Keywords: TOLL-LIKE RECEPTORS; BCG VACCINATION; ENVIRONMENTAL MYCOBACTERIA; TUBERCULIN REACTIVITY; IMMUNOGLOBULIN-E; AIRWAY HYPERRESPONSIVENESS; INVERSE ASSOCIATION; CELLULAR ACTIVATION; ALLERGIC RESPONSE; IMMUNE-RESPONSES